Calix[4]arene amine modified silica: from fundamentals to new recyclable materials for the removal of chlorophenoxy acids from water - Danil de Namor, Angela F. (2015)
Two molecular receptors based on calix[4]arenes and their interaction with chlorophenoxy acid herbicides in solution and in the solid state have been investigated. From 1H NMR studies it is shown that the conformational changes of the receptor are directly related to the acid strength of the herbicide. Conductance data show that the interaction takes place through a proton transfer reaction from the herbicide to the receptor. This is also reflected in the solid state (X-ray crystallography). Based on these fundamental studies, these receptors were immobilised by grafting them into a silica based solid support. The extracting properties of calix[4]arene modified silica for these pollutants were investigated as a function of the pH of the aqueous solution and the capacities of these materials to remove these pollutants are reported. Titration calorimetry is for the first time explored to determine the factors (kinetics, mass/solution ratio and temperature) contributing to the optimal removal of herbicides from water. These materials can be easily recycled via a pH switching mechanism. After several recycling processes the extraction capacity of these materials remains at the level of 80–90% of the original value.